OPTIMALISASI PENGOLAHAN DATA REKAM MEDIS UNTUK MENINGKATKAN KUALITAS KADER POSYANDU DAN LITERASI KMS PADA IBU BALITA - Evina Widianawati; Widya Ratna Wulan (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
In maximizing the growth and development of children, the medical record data processing needs to be done optimally. This study aims to improve the quality of Posyandu cadres and KMS literacy through optimization of Posyandu medical record data processing. The research design used is quantitative research. The population is the cadres of Posyandu and the community in Kedungori Village, Dempet Demak as many as 78 people. Research variables include: Quality of Posyandu cadres (X) and KMS Literacy in mothers of children under five (Y). Data were analyzed using descriptive analysis and Wilcoxon test for variables X and Y. The results showed that optimization of medical record data processing was able to improve the quality of posyandu cadre services and KMS literacy in mothers. The most significant improvement in the quality of cadre services is active cadres providing health information on the results of measurements of baby's weight and height to the mother. The most significant increase in KMS literacy is being able to read the KMS chart and find out the meaning of the KMS chart. Keywords: Cadres, Literation, Medical Record, Posyandu, Quality